Characterization of FtsH Essentiality in Streptococcus mutans via Genetic Suppression - Wang, Yaqi; Cao, Wei; Merritt, Justin; Xie, Zhoujie; Liu, Hao (Frontiers in Genetics, 2021)
FtsH belongs to the AAA+ ATP-dependent family of proteases, which participate in diverse cellular processes and are ubiquitous among bacteria, chloroplasts, and mitochondria. FtsH is poorly characterized in most organisms, especially compared to other major housekeeping proteases. In the current study, we examined the source of FtsH essentiality in the human oral microbiome species Streptococcus mutans, one of the primary etiological agents of dental caries. By creating a conditionally lethal ftsH mutant, we were able to identify a secondary suppressor missense mutation in the vicR gene, encoding the response regulator of the essential VicRK two-component system (TCS). Transcriptomic analysis of the vicR (G195R) mutant revealed significantly reduced expression of 46 genes, many of which were located within the genomic island Tnsmu2, which harbors the mutanobactin biosynthetic gene cluster. In agreement with the transcriptomic data, deletion of the mutanobactin biosynthetic gene cluster suppressed ftsH essentiality in S. mutans. We also explored the role of FtsH in S. mutans physiology and demonstrated its critical role in stress tolerance, especially acid stress. The presented results reveal the first insights within S. mutans for the pleiotropic regulatory function of this poorly understood global regulator.